Analysis of bending of composite I-beams - Ng, Lui Pang (Nanyang Technological University, 2024)
This Final Year Project aims to carry out analysis of the bending of composite I-beams using a Finite Element Analysis (FEA) software called ANSYS Workbench. Two beam models are set up from Carbon Fibre Reinforced Polymer (CFRP) and Toray T700S each, in 8-ply ad 4-ply. The software is used to simulate a 3-point bending test on the models to study its effects of the I beams, and comparisons will be made to similar studies to find out how the differing parameters has affected the outcome of the simulation. Convergence study was conducted in an effort to increase accuracy and reliability of results. Graphs of stress-strain curves and force deflection are plotted to illustrate the results from the simulation. As seen from previous studies conducted on these two materials, Toray T700S makes stiffer and more elastic models than CFRP, which results in a more durable I-beam. The study conducted here will be to investigate how different ply orientation affects the durability of said models.